Workshop Literasi Penggunaan Media Sosial dalam Promosi UMKM di desa Karang Tengah Kabupaten Bengkulu Tengah - Rahayu, Novi; Yulyani, Cici; Tarnando, Mardi; Bilal, Anggi Mustafa; Andila, Andila (Universitas Dehasen Bengkulu, 2021)
Digital literacy is used to find, analyze, create and transmit information using technology. Based on the experience of several countries, the use of information technology has become one of the drivers of economic development, especially in rural areas. ICT utilization is considered effective in reducing community migration from villages to cities and increasing Micro, Small and Medium Enterprises (MSMEs) in the village. The existence of MSMEs itself can support the development of tourism in the village. This PKM is organized to help overcome problems related to increasing digital literacy competencies to improve MSME promotion in the aspect of digital marketing communication strategies.